Research on Soil Carbon Storage of Alpine Grassland under Different Uses in Qinghai-Tibet Plateau - Li, Tao; Gan, Youmin; Ji, Lei; Yang, Shujing; Song, Zhongqi (UKnowledge, 2020)
In recent years, with the temperature rising on the Qinghai-Tibet Plateau, studies have shown that (Shaoqing Wang et al. 1999; Yuchun Qi et al. 2003) the plateau permafrost has great potential for emissions of greenhouse gases such as carbon, nitrogen, because of the remarkable permafrost thermal sensitivity. The Qinghai-Tibet Plateau is a special geographical and ecological unit, which has an important role in global climate change. The study of soil carbon storage of grassland ecosystems in the Qinghai-Tibet Plateau and its distribution characteristics allow the evaluation of different land management. The carbon cycle response and feedback effects of the whole terrestrial ecosystems have important scientific value to the global carbon cycle and global climate change.